Efektivitas Augmentative and Alternative Communication Berbasis Picture Exchange Communication System terhadap Penurunan Perilaku Tantrum Pada Anak Nonverbal: Studi Kuasi-Eksperimen - Anisyah Dewi Syah Fitri; Dodiet Aditya Setyawan (Jurnal Terapi Wicara dan Bahasa, 2026)
Background: Communication barriers in nonverbal children often lead to difficulties in expressing their needs and wants effectively. This condition may result in tantrum behavior as a form of maladaptive communication arising from communication-related frustration. Augmentative and Alternative Communication (AAC), particularly the Picture Exchange Communication System (PECS), is an intervention developed to improve functional communication while reducing problem behaviors. Although the effectiveness of AAC in enhancing communication skills has been widely studied, empirical evidence regarding its influence on reducing tantrum behavior among nonverbal children in Indonesia remains limited. Objectives: To analyze the effectiveness of PECS-based AAC in reducing the frequency and duration of tantrum behavior in nonverbal children aged 7–8 years. Methods: This study employed a quasi-experimental design using a one-group pretest–posttest approach. The sample consisted of 15 nonverbal children aged 7–8 years, selected through purposive sampling. The intervention, which involved PECS, was administered for eight weeks at a frequency of three sessions per week. The frequency and duration of tantrum behavior were measured using observation sheets before and after the intervention. Data were analyzed descriptively, while hypothesis testing was conducted using the Wilcoxon Signed Rank test at a significance level of 5%. Results: The average frequency of tantrums decreased from 24.33 to 1.87 episodes per week, and the average duration of tantrums decreased from 13.33 to 2.87 minutes per episode. The Wilcoxon test results revealed a significant difference between conditions before and after the intervention (p < 0.05), with a large effect size. Conclusion: PECS-based AAC is effective in reducing the frequency and duration of tantrum behavior in nonverbal children. These findings indicate that providing functional communication tools can reduce maladaptive behaviors triggered by communication barriers. AAC may be considered as one of the interventions in speech therapy practice to improve communication skills and support behavioral management in nonverbal children. Keywords: Augmentative And Alternative Communication, PECS, Nonverbal Children, Tantrum, Speech Therapy.